High-order sliding mode control for variable speed PMSG-wind turbine-based disturbance observer. (29th August 2019) - Ayadi, Marwa; Naifar, Omar; Derbel, Nabil
This paper introduces a model-based control system for variable speed wind energy conversion system (VSWECS)-based permanent magnet synchronous generator (PMSG). Comparing to traditional wind turbines operating methods, these variable speed systems have the advantages of increasing the energy capture and reducing the mechanical stress. In order to exploit this latest advantage, a high order sliding mode (HOSM) control strategy has been developed to enhance system performances, ensure the maximum power point tracking (MPPT) and track the generator reference speed. Moreover, for the WT system, the turbine torque is considered as an immeasurable disturbance. Therefore, using a modified disturbance observer will allow direct tracking of the maximum power point. The stability analysis of the system has been proved using the Lyapunov theory. Finally, simulation results have been presented to verify the proposed approach efficiency.